AWARENESS AND PERCEPTION OF UNDERGRADUATE STUDENTS TOWARD PLAGIARISM IN MOSHOOD ABIOLA POLYTECHNIC (NAU Journal of Library and Information Science, 2022)
This study investigated the awareness and perception of plagiarism among undergraduate students in Moshood Abiola Polytechnic, Abeokuta, Ogun State. Five research questions guided the study. The research design was a survey. A multi-stage random sampling was adopted to select respondents for the study. The first stage involved selecting the Mass Communication Department from the Faculty of Arts using random sampling, while the final stage involved selecting 229 Higher National Diploma 11 students from among 534 students of the Polytechnic understudy using purposive sampling. Instrument for data collection was a questionnaire. Out of the 229 copies of questionnaire administered 195 (85%) copies were properly filled and found usable for the study.  Data was analysed using descriptive statistics and Pearson Product Moment Correlation (PPMC). The findings of the study revealed that students have high level of awareness about plagiarism. Forms of plagiarism include direct copying, giving incorrect information about source. The perception of students regarding plagiarism differs. While some see it as a serious offence, others see it as a minor offence. Reasons of plagiarizing include lack of knowledge and understanding about plagiarism, and teachers’ unclear instruction about academic integrity.) Based on the findings, the study recommends that, seminars on plagiarism should be organized by management of the institutions; lecturers should take plagiarizing in assignments as a serious offence. The study also recommended that plagiarism can be reduced to the barest minimum through awareness creation and introducing the Turnitin plagiarism software in Moshood Abiola Polytechnic, Ogun State.
Keywords: Plagiarism; Awareness Creation; Students Perception; Moshood Abiola Polytechnic; Abeokuta